Design Of Teller Performance Assesment Application Using Fuzzy Logic With Sugeno Method - Jhonson Tanadi (IHSA Institute, 2021)
The teller performance assessment used by several banks still uses performance parameters that cannot be measured properly. Fuzzy logic using the Sugeno method can be applied to evaluate more measurable performance parameters. This paper describes the design of a teller performance assessment application in a fuzzy logic-based bank using the Sugeno method. As parameters for performance indicators, 4 parameters were chosen: time discipline, behavior attitude, work performance, and achievement from the teller. The output of the application is the performance value of the assessment object (teller) which can be used for further needs.